Gender perspective of parental role model influence on nascent entrepreneurs: Evidence from Colombia - Jorge Moreno-Gómez; Eduardo Gómez-Araujo; Daiwer Ferrer-Ortíz; Ricardo Pe\~na-Ruiz (European Research on Management and Business Economics (ERMBE), 2022)
We examine the effect of parental entreprenurial role model in nascent entrepreneur's activity by gender perspective. We distinguish between father and mother entreprenurial role models and investigate how their influence on students' decision to become nascent entreprenuer activity is moderated by gender We employ a logit model on a sample of 15.424 university students from Colombia GUESSS 2018. The findings show not only that the presence of parental entreprenurial role model impact the decision to become nascent entrepreneur, but also the effect of this impact is moderated by gender. This effect is significant in the case of father entrepreneurial role model. We discuss the implications of our findings for research on entrepreneurial families and parental role models.
Keywords: M13; J16; 650; Entrepreneurship; Gender; Nascent entrepreneur; Parental entreprenurial role model